Study concerning traumatic injuries of the lower limbs in top gymnasts - Untea, G. H.; Costeschi, I.; Anghelescu, M.; Ovricenco, M. (1999)
Between 1981-1996, during a period of 4 Olympic cycles, gymnastics was on the 4-th place regarding the number of sports injuries after athletics, football and rugby as followed from a previous study of the Traumatology and Rehabilitation Laboratory of the National Sports Medicine Institute - Romania. Although the Romanian Olympic Gymnastics Team is a small one, the high traumatic morbidity, especially of the lower limb -62%- determined us to a thoroughgoing study. In these 16 years out of 3182 sports injuries, 48.4% involved soft tissues, the majority of the thigh,21.9% involved the bones, especially of the shank and 29.7% were injuries of the joints. Out of the 525 soft tissue injuries, the most frequent were: 1. Contusions - 38% (189). 2. Tendinitis - 25% (131) - the most common of the achille`s tendon. 3. Partial muscle ruptures -12% (63) - especially on the posterior side of the thigh. Bone injuries 238 1.pain of calcaneus -26% (62) 2.epiphysitis - 16% (38) The most frequent joint injuries (684)- were: 1.sprains -39% (260), especially of the ankle 2.joint laxity of the knee -21% (150) 3.meniscal injuries - 18% (123), 4% of them associated with cruciate ligaments injuries. Out of the 3182 sports injuries, 62 needed surgery: meniscal injuries with or without ruptures of the cruciate ligaments, chondropaties of the joint surface of the femur, chondromalacia patellae and others. The most frequent causes of the sports injuries were: the direct impact, microtraumatisms associated with metabolic disorders, and stress injuries.